Early antituberculosis drug exposure in hospitalized patients with human immunodeficiency virus‐associated tuberculosis. Issue 5 (17th February 2020) - Schutz, Charlotte; Chirehwa, Maxwell; Barr, David; Ward, Amy; Janssen, Saskia; Burton, Rosie; Wilkinson, Robert J.; Shey, Muki; Wiesner, Lubbe; Denti, Paolo; McIlleron, Helen; Maartens, Gary; et al.
Abstract : Aims: Patients hospitalized at the time of human immunodeficiency virus‐associated tuberculosis (HIV‐TB) diagnosis have high early mortality. We hypothesized that compared to outpatients, there would be lower anti‐TB drug exposure in hospitalized HIV‐TB patients, and amongst hospitalized patients exposure would be lower in patients who die or have high lactate (a sepsis marker). Methods: We performed pharmacokinetic sampling in hospitalized HIV‐TB patients and outpatients. Plasma rifampicin, isoniazid and pyrazinamide concentrations were measured in samples collected predose and at 1, 2.5, 4, 6 and 8 hours on the third day of standard anti‐TB therapy. Twelve‐week mortality was ascertained for inpatients. Noncompartmental pharmacokinetic analysis was performed. Results: Pharmacokinetic data were collected in 59 hospitalized HIV‐TB patients and 48 outpatients. Inpatient 12‐week mortality was 11/59 (19%). Rifampicin, isoniazid and pyrazinamide exposure was similar between hospitalized and outpatients (maximum concentration [Cmax ]: 7.4 vs 8.3 μg mL –1, P = .223; 3.6 vs 3.5 μg mL –1, P = .569; 50.1 vs 46.8 μg mL –1, P = .081; area under the concentration–time curve from 0 to 8 hours: 41.0 vs 43.8 mg h L –1, P = 0.290; 13.5 vs 12.4 mg h L –1, P = .630; 316.5 vs 292.2 mg h L –1, P = .164, respectively) and not lower in inpatients who died. Rifampicin and isoniazid Cmax were below recommended ranges in 61% and 39% of inpatients and 44% and 35% of outpatients. Rifampicin exposure was higher in patients with lactate >2.2 mmol L –1 . Conclusion: Mortality in hospitalized HIV‐TB patients was high. Early anti‐TB drug exposure was similar to outpatients and not lower in inpatients who died. Rifampicin and isoniazid Cmax were suboptimal in 61% and 39% of inpatients and rifampicin exposure was higher in patients with high lactate. Treatment strategies need to be optimized to improve survival.